2020
DOI: 10.1128/mra.00817-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Enterobacteriales Strains Isolated from the International Space Station

Abstract: The whole-genome sequences of 26 strains isolated from the International Space Station were generated, and the strains were identified as being members of the order Enterobacteriales. Characterization of these whole-genome sequences might enable the identification of potential pathogenic bacteria that have been adapting to the space environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Candidate flight species to use in our analysis were determined from literature 42 44 . Isolates from the ISS were identified in the NCBI databases 18 by searching the BioSample database for “geo_loc_name=USA: International Space Station”[attr] AND “SPECIES NAME”.…”
Section: Methodsmentioning
confidence: 99%
“…Candidate flight species to use in our analysis were determined from literature 42 44 . Isolates from the ISS were identified in the NCBI databases 18 by searching the BioSample database for “geo_loc_name=USA: International Space Station”[attr] AND “SPECIES NAME”.…”
Section: Methodsmentioning
confidence: 99%
“…Candidate ight species to use in our analysis were determined from literature (43)(44)(45). Isolates from the ISS were identi ed in the NCBI databases (18) by searching the BioSample database for "geo_loc_name = USA: International Space Station"[attr] AND "SPECIES NAME".…”
Section: Flight and Terrestrial Genomesmentioning
confidence: 99%
“…Previous attempts to isolate microorganisms from ISS environmental surfaces revealed that they generally consist of predominantly benign and commensal microorganisms ( Mhatre et al, 2020 ; Bijlani et al, 2021 ), but potentially pathogenic microorganisms were also sporadically isolated ( Knox et al, 2016 ; Singh et al, 2018a ). In 2015, several bacterial strains were collected from the observation deck (Cupola) of the ISS, and whole-genome sequences (WGS) were generated for these isolates ( Bharadwaj et al, 2020a , b ; Bijlani et al, 2020a , b ; Daudu et al, 2020a , b ; Solomon et al, 2020 ; Simpson et al, 2021 ). Based on preliminary genomic analyses, three ISS strains were identified as belonging to the Agrobacterium genomospecies 3 (also known as A. tumefaciens genomovar G3 or Agrobacterium G3).…”
Section: Introductionmentioning
confidence: 99%